Linguistic complexity of arabic language: a semantic analysis of antonymous homonyms in the holy Qur'ān - Dollah, Nafi@Hanafi; Alfa, Muhammed Salisu (2015)
Homonymy, is one of the two main sub-divisions of lexical ambiguity that represents the complex nature of form and context of the Qur'anic Arabic which presents a challenge in the translation process. Since Qur'anic discourse abounds with homonymic expressions whose meaning is derived from the context, the translators of the Qur'an should undertake a demanding task decoding the intended meanings. The present paper aims at clarifying some linguistic complexities in some verses of the Qur'ān which may pose difficulty to translators of the holy book most especially those who are not familiar with antonymous homonyms in Arabic language. The reason is that antonymous homonyms are special features of the Qurʾanic Arabic language. It may be viewed as one of the stylistic feature of the Qur'an. Therefore, classification of these linguistic complexity is offered and the samples of these classifications from the Holy Qur'ān are mentioned in relation to antonymous homonyms. Samples of translated Qur'an are compared in order to ascertain the qualities of translations and English translation strategies of the stated verses.